An unyielding valve leading to venous spasm during pacemaker implantation: a case report. Issue 4 (27th September 2019) - Krishnappa, Darshan; Sakaguchi, Scott; Kasinadhuni, Ganesh; Tholakanahalli, Venkatakrishna N
Abstract: Background: Subclavian venous spasm is an uncommon complication during permanent pacemaker implantation. The exact aetiology of subclavian venous spasm is not clear but has been suggested to be due to either mechanical irritation of the vein during needle puncture or due to chemical irritation from contrast injection. Here, we report a case of an unyielding subclavian vein valve that impeded guidewire advancement and the repeated guidewire manipulation led to venous spasm. Case summary: A 45-year-old woman with a history of surgical repair of Tetrology of Fallot in childhood presented with symptomatic bifascicular block and underwent a permanent pacemaker implantation. A subclavian venogram done prior to the procedure showed a prominent valve in the distal portion of the vein. Following venous puncture, guidewire advancement was impeded by the prominent valve. The resulting guidewire manipulation led to subclavian venous spasm necessitating a medial subclavian venous puncture and access. Discussion: Prolonged mechanical irritation of the vein during pacemaker implantation may lead to venous spasm impeding pacemaker implantation. Early identification of an impeding valve and obtaining access medial to the valve may help prevent this uncommon complication.